Application of Remap-STAD Learning Model to Improve Student Cognitive Learning Outcomes in Teaching and Learning Strategy Course - Sari, Tri Maniarta; Ernawati, Ernawati; Amaliah, Nur (Universitas Sulawesi Barat, 2023)
Monotonous learning process in this case the use of conventional methods that continuously have a significant enough effect on learning outcomes, therefore innovation is needed in carrying out the learning process in the classroom. regards, one innovation is using a new learning model, namely by using Remap-STAD learning model. This study aims to see the improvement of student cognitive learning outcomes who are taught using the Remap-STAD learning model. This research was conducted at Sembilanbelas November Kolaka University. The sample of this study was students of class 2018 offering B who program the Teaching and Learning Strategy course with a total of 27 students. This study used a qualitative approach to the type of classroom action research combined with Lesson Study. Data on cognitive learning outcomes are obtained through essay tests that are supported by observations. The results of this study indicate an increase in the cognitive learning outcomes of students who are taught with the Remap-STAD learning model.